Drone warfare killing by remote control - Benjamin, Medea 1952- (Verso, 2013)
Drone Warfare is the first comprehensive analysis of one of the fastest growing-and most secretive-fronts in global conflict: the rise of robot warfare. In 2000, the Pentagon had fewer than fifty aerial drones; ten years later, it had a fleet of nearly 7,500, and the US Air Force now trains more drone "pilots" than bomber and fighter pilots combined. Drones are already a $5 billion business in the US alone. The human cost? Drone strikes have killed more than 200 children alone in Pakistan and Yemen.